Scientific And Theoretical Significance Of The Principles And Methods Of Water Legislation In Uzbekistan - Khayitov Khasan Shermatovich (Zien Journals, 2022)
In general, the principles of water legislation will be aimed at defining the goals and objectives of the legal regulation of the rational use and protection of water. The basic principles of water legislation are based on the natural laws of water and serve to correctly define the rights and obligations of water users in relation to water resources
Keywords: Water legislation; legal regulation administrative; criminal; civil